A Study on Screen Adaptations from Literature with Reference to Chetan Bhagat’s Novel - Kaur, Manmeet; Kapoor, Divya Rastogi (Journal of Advanced Research in Journalism & Mass Communication, 2018)
In order to cater a huge audience, film makers from all over the world have adopted literature writings for movie making. The key purpose of these screen adaptations lies in giving visual appeal to the black and white words of the author’s writings. Furthermore, there are restricted readers for different genres and subject of novel and literature respectively. But film making satisfies the hunger of a large heterogeneous audience with the element of ‘entertainment’. The idea of screen adaptations dates back years ago when people had limited options for entertainment and recreational activities. The study is based on movies made in Bollywood which have been inspired by the writings of novelists. This is a qualitative research in which Chetan Bhagat’s novel ‘Five Point Someone’ and ‘2 States’have been take up by Bollywood filmmakers to make movies ‘3 Idiots’ and ‘2 States’ respectively. The research methodology will be content analysis that how writer’s experience with words can make movie audience fall for it through the adaptations. How to cite this article: Kaur M, kapoor DR. A Study on Screen Adaptations from Literature with Reference to Chetan Bhagat’s Novel. J Adv Res Jour Mass Comm 2018; 5(1&2): 1-6. DOI: https://doi.org/10.24321/2395.3810.201801